STUDY OF BENTONITE ACTIVATION USING SULFURIC ACID AND ITS APPLICATION AS AN ADSORBENT OF RHODAMINE B DYE - Catherina M. Bijang; Dewi Sri (Pattimura University, 2017)
A study about activated bentonite with 2M, 3M, 4M Sulfuric Acid and its application as a Rhodamin dye adsorbent had been done. Bentonite was saturated with 3M NaCl before activated by acid. Performance determination of adsorbent is done by using Uv-Vis Spectrophotometric method. Concentrate determination of Rhodamin B dye made at a wavelength of 554 nm. The result obtained showed that the 2M sulfuric acid bentonite is the best adsorbent.